Research Field on Migration in Chile. Review, Reflections and Proposal for a Classification. 2010-2023; [Campo Investigativo de Las Migraciones en Chile. Revisión, Reflexiones y Propuesta Para Una Clasificación. 2010-2023] - Torres-Ortega, J (Arturo Prat University, 2025)
International migration has been a process that has gained considerable attention from the academic world in recent years in Chile. Various disciplines, approaches, methodologies and theories have contributed to the construction of a body of accumulated knowledge in migration studies. Based on the review of academic literature obtained from WoS and Scopus between 2010 and 2023 following the guidelines of the PRISMA Declaration, the most recurrent topics in research are identified and analyzed, using keyword co-occurrence criteria to map the main areas of study. From these analyses, three categories are proposed to classify the accumulated knowledge: (1) the interactions of migrants with the host society, focused on economic, social and cultural integration; (2) the relationship between migrants and the State, which encompasses institutional responses, national policy design and international cooperation; and (3) the behavior of migratory flows, analyzing the trends, causes, patterns and consequences of human mobility in the country. The article concludes that, although certain topics such as gender and education have achieved considerable development, there are less explored areas that present opportunities for future research. In addition, it highlights the need for a more comprehensive and coordinated approach to migration governance, which reflects the complexities of the migration phenomenon in Chile and its impact on society. © 2025 Byron Duhalde, Gorka Moreno y Jorge Torres-Ortega.
Keywords: migrations; Chile; systematic review; migration policies